PELAKSANAAN KEWENANGAN PENGHULU DALAM PENGANGKATAN DAN PEMBERHENTIAN PERANGKAT KEPENGHULUAN TELUK MEGA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR TAHUN 2021 - Pratiwi, Aulia; Hadi, Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research discusses the Implementation of the Headman's Authority in the Appointment and Dismissal of the Teluk Mega Village Administration in Tanah Putih District, Rokan Hilir Regency, in 2021. The issue that arises in this research is the unilateral dismissal of village officials by the village head. The purpose of this study is to understand the Implementation of the Village Head's Authority in the Appointment and Dismissal of Village Officials in Teluk Mega, Tanah Putih District, Rokan Hilir Regency in 2021. This research uses the Authority Theory proposed by Muhammad Muiz Raharjo (2021), which includes the Authority and Duties of the Penghulu, the Authority to Appoint Village Administration Staff, and the Authority to Dismiss Village Administration Staff. This research uses a descriptive qualitative research method with the main data sources being primary and secondary data. The data collection techniques used are interview techniques and documentation techniques. The data analysis techniques are Data Reduction, Data Presentation, and Conclusion Drawing. The results of this study found that the process of Appointment and Dismissal of Village Officials was not based on the Minister of Home Affairs Regulation Number 67 of 2017 concerning Appointment and the Regional Regulation of Rokan Hilir Regency Number 10 of 2015 concerning Appointment and Dismissal of Village Officials, and was carried out unilaterally without any clear legal basis. Keywords: Authority and Duties of the Headman, Authority to Appoint Village Officials, Authority to Dismiss Village Officials